Airway management in Escobar syndrome: A formidable challenge - Shaji Mathew; Souvik Chaudhuri; H D Arun Kumar; Tim Thomas Joseph (Indian Journal of Anaesthesia, 2013)
Escobar syndrome is a rare autosomal recessive disorder characterized by flexion joint and digit contractures, skin webbing, cleft palate, deformity of spine and cervical spine fusion. Associated difficult airway is mainly due to micrognathia, retrognathia, webbing of neck and limitation of the mouth opening and neck extension. We report a case of a 1 year old child with Escobar syndrome posted for bilateral hamstrings to quadriceps transfer. The child had adequate mouth opening with no evidence of cervical spine fusion, yet we faced difficulty in intubation which was ultimately overcome by securing a proseal laryngeal mask airway (PLMA) and then by intubating with an endotracheal tube railroaded over a paediatric fibreoptic bronchoscope passed through the lumen of a PLMA.